CFD simulation of solids carrying capacity of a newtonian fluid through horizontal eccentric annulus - Osgouei, R.E. (2013)
It is essential to transport cuttings generated in drilling operations to the surface for disposal. As the inclination of wellbore increases, cuttings begin to deposit in the lower section of the wellbore, and develop cuttings bed. This developed bed increases the mechanical friction between the drillstring and the wellbore. As a result, problems such as increase in torque, decrease in force transfer to the bit, and poor control of the bottom hole pressure arise. Estimation of total concentration of cuttings inside the wellbore has never been an easy task. Cuttings and fluid dragging them to be transported have different relative velocities inside the wellbore, causing variations in pressure drop. Hence, a better understanding in cuttings - liquid interactions inside the wellbore is required. In this study, the interactions between cuttings and drilling fluid in horizontal eccentric annulus were simulated and observed using commercial Computational Fluid. CFD software program has proven to be a successful tool in studying complex fluid mechanic problems that are difficult to solve analytically. The effect of fluid flow rate and the impact of the rate of penetration (ROP) on flow patterns, cuttings concentration and pressure losses were investigated and validated using data obtained from Middle East Technical University Petroleum and Natural Gas Engineering Department Cuttings Transport / Multiphase Flow Loop. The drilling fluid of study is limited to water, a Newtonian fluid. The results obtained from the simulations show good agreement with the experiments. As the drilling fluid flow rate increases, the flow pattern was observed changing from stationary bed to dispersed flow, which complies with experimental results and literature findings. Increase in flow rate overcomes the gravitational force that pulls the cuttings downward and increases the surface forces that lift the cuttings up to the surface. Consequently, by increasing annular flow rate, cuttings concentration is decreased. On the other hand, the increment in ROP leads to more cuttings generated and more cuttings accumulation in the well bore. In conclusion, fluid flow rate and ROP are both significant factors in hole cleaning operations. The higher the flow rate, the higher the efficiency of hole cleaning, whereas the higher the ROP, the less efficient is the hole cleaning. CFD is proven to be successfully applied to predict the solid concentration in the well. Therefore this tool can be used for more complex cases, and the information provides can be very useful especially when there is no any other data available. Copyright Â© 2013 by ASME.